Non-semitic loanwords in the Hebrew Bible: a lexicon of language contact - Noonan, Benjamin J. (Linguistic Studies in Ancient West Semitic, 2021)
Frontmatter -- Contents -- Tables -- Acknowledgments -- Abbreviations -- Entries -- Part 1: Loanwords and the Contexts of Contact -- Chapter 1. Introduction -- Chapter 2. Non- Semitic Contact in Ancient Palestine -- Part 2: Non- Semitic Loanwords in the Hebrew Bible -- Chapter 3. Non- Semitic Loanwords in the Hebrew Bible -- Part 3: Analysis -- Chapter 4. Quantitative Analysis -- Chapter 5. Linguistic Analysis -- Chapter 6. Evidence for Dialect of Origin and Date of Borrowing -- Chapter 7. Non- Semitic Loanwords as Evidence for Foreign Contact in Ancient Palestine -- Epilogue -- Appendix: Words Incorrectly Identified as Non- Semitic Loans -- Bibliography -- Index of Authors -- Index of Scripture -- Index of Ancient Sources -- Index of Words